2019
DOI: 10.1037/xlm0000574
|View full text |Cite
|
Sign up to set email alerts
|

Strategy selection versus flexibility: Using eye-trackers to investigate strategy use during mental rotation.

Abstract: Spatial researchers have been arguing over the optimum cognitive strategy for spatial problem-solving for several decades. The current article aims to shift this debate from strategy dichotomies to strategy flexibility—a cognitive process, which although alluded to in spatial research, presents practical methodological challenges to empirical testing. In the current study, participants’ eye movements were tracked during a mental rotation task (MRT) using the Tobii ×60 eye-tracker. Results of a latent profile a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
46
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(59 citation statements)
references
References 74 publications
(150 reference statements)
7
46
1
5
Order By: Relevance
“…Another argument supporting differential processing of stimuli in a mental rotation task is the fact that the fixation patterns have been shown by Nazareth et al (2019) to differ. In their recently published study, the participants' eye movements during an object-based mental rotation task with abstract figures were tracked (Nazareth et al 2019).…”
Section: Mental Rotation In An Object-based Transformation Task With mentioning
confidence: 99%
See 2 more Smart Citations
“…Another argument supporting differential processing of stimuli in a mental rotation task is the fact that the fixation patterns have been shown by Nazareth et al (2019) to differ. In their recently published study, the participants' eye movements during an object-based mental rotation task with abstract figures were tracked (Nazareth et al 2019).…”
Section: Mental Rotation In An Object-based Transformation Task With mentioning
confidence: 99%
“…Another argument supporting differential processing of stimuli in a mental rotation task is the fact that the fixation patterns have been shown by Nazareth et al (2019) to differ. In their recently published study, the participants' eye movements during an object-based mental rotation task with abstract figures were tracked (Nazareth et al 2019). The results (latent profile analysis that combined different eye movement parameters) indicated two distinct eye-patterns: fixating (indicating a holistic strategy) and switching (indicating a piecemeal strategy).…”
Section: Mental Rotation In An Object-based Transformation Task With mentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of mental rotation, reported sex differences in spatial skills are typically small (Nazareth, Huang, Voyer, & Newcombe, 2019) and/or do not emerge until after puberty (Voyer, Voyer, & Bryden, 1995). While the basis for sex differences in spatial cognition is still debated, recent explanations suggest that males have more spatial experience (i.e., wayfinding experience) than females do (Lawton & Kallai, 2002;Schug, 2016b), that different strategies for solving spatial problems may contribute to sex differences (Lawton, 1994(Lawton, , 1996Nazareth, Killick, Dick, & Pruden, 2019;Stieff, Dixon, Ryu, Kumi, & Hegarty, 2014), and that wayfinding-specific spatial anxiety is related to both perceived and actual navigation ability (Lyons et al, 2018). In the current study, we examined the relationships between self-reported childhood wayfinding experience, the use of different wayfinding strategies, and wayfinding anxiety with the goal of explaining sex and individual differences.…”
Section: Introductionmentioning
confidence: 99%
“…Structural breaks and changepoints occur in time series data arising from a variety of fields, including medicine, 1 environment, 2,3 psychology, 4 and finance 5 . A key goal in many applications is to understand the dynamics of a time series to produce accurate forecasts into the future.…”
Section: Introductionmentioning
confidence: 99%